Forord - Preface - Skjenneberg (ed.), Sven (Rangifer, 1986)
The third yearly conference of Nordic reindeer researcher was organized by Nordic Council for Reindeer Research in Rovaniemi, Finland, October 15-17, 1986. The conference was to a high degree marked by the Chernobyl reactor accident which had caused serious fallout problems to the reindeer industry in Fennoscandia, especially in Norway and Sweden. The conference language was Scandinavian, but a lot of the manuscripts are delivered in English. All presentations and debates on the first day of the conference were recorded on a tape recorder. The reports are partly done by the editor on the basis of these records. The lecturers were given opportunity to correct and accept the reports.
Keywords: Nordic reindeer conference; 1986; Raovaniemi; Finland; Chernobyl; reactor accident